Prevalency of academic dishonesty among high school students in Zimbabwe - Kasayira, Joseph M.; Makore, Jowas; Chipandambira, Kudzai S.; Maseko, Mpikelelo M.; Tuturu, Tsitsi N. (Midlands State University, 2015)
The study sought to identify common methods of academic cheating, situations when academic dishonesty took place and the perceived reasons for engaging in such behaviours. Form 5 and Form 6 students sampled from 4 Gweru urban high schools (n=238) responded to a questionnaire that was used to collect data. A descriptive survey design was used and the data were analysed using frequency counts and percentages. The results indicated that academic cheating was common among all sampled schools with male students more involved. It was also revealed that some officials were involved in assisting students to cheat. The findings of this study have implications that can assist in developing effective approaches to prevent and reduce academic dishonesty in high schools